2022
DOI: 10.3390/molecules27165119
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the N-Glycosylation of the SARS-CoV-2 S Protein Contained in VLPs Produced in Nicotiana benthamiana

Abstract: The emergence of the SARS-CoV-2 coronavirus pandemic in China in late 2019 led to the fast development of efficient therapeutics. Of the major structural proteins encoded by the SARS-CoV-2 genome, the SPIKE (S) protein has attracted considerable research interest because of the central role it plays in virus entry into host cells. Therefore, to date, most immunization strategies aim at inducing neutralizing antibodies against the surface viral S protein. The SARS-CoV-2 S protein is heavily glycosylated with 22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 34 publications
0
12
1
Order By: Relevance
“…Other studies have also reported reduced mannose processing in plants for viral glycoproteins ( Dobrica et al., 2021 ; Margolin et al., 2021a ), although the extent to which processing was arrested here remains a surprise. Interestingly the N-glycosylation pattern observed for the plant-produced spike in this study contrasts with a recent report describing the production of virus-like particles bearing the full-length protein in wild type N. benthamiana ( Balieu et al., 2022 ). In the study conducted by Balieu et al., highly processed mature N-glycans were observed, including typical plant-derived complex glycans with Lewis A epitopes, contrasting against the abundance of immature oligomannose N-glycans that we observed.…”
Section: Discussioncontrasting
confidence: 99%
“…Other studies have also reported reduced mannose processing in plants for viral glycoproteins ( Dobrica et al., 2021 ; Margolin et al., 2021a ), although the extent to which processing was arrested here remains a surprise. Interestingly the N-glycosylation pattern observed for the plant-produced spike in this study contrasts with a recent report describing the production of virus-like particles bearing the full-length protein in wild type N. benthamiana ( Balieu et al., 2022 ). In the study conducted by Balieu et al., highly processed mature N-glycans were observed, including typical plant-derived complex glycans with Lewis A epitopes, contrasting against the abundance of immature oligomannose N-glycans that we observed.…”
Section: Discussioncontrasting
confidence: 99%
“…The N -glycan profiles of NB-RBD and BY2-RBD were then determined through a glycoproteomic approach as previously described in Balieu et al. (2022) .…”
Section: Resultsmentioning
confidence: 99%
“…In order to determine the respective N -glycan profiles of both RBD samples and their distribution on these two N ‐glycosylation sites, the mixtures of peptides and glycopeptides released by the endoprotease digestions were submitted to a targeted LC-ESI MS/MS analysis ( Balieu et al., 2022 ). To this end, peptides giving MS/MS spectra exhibiting N ‐glycan diagnostic fragment ions at m/z 204 ( N ‐acetylglucosamine) and 366 (Man‐GlcNAc) were selected as being glycopeptides.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These plant-based vaccines showed high immunogenicity and were well-tolerated in phase I, II, and III clinical trials [95,96]. However, other reports have revealed that the plant-produced vaccine contained plant-specific N-glycan epitopes that could cause immunogenic or allergic reactions in humans [97,98]. Recently, the potential of the bacteria Escherichia coli and the yeast Pichia pastoris was evaluated for the production of SARS-CoV-2 RBD fragments [99,100].…”
Section: Potential Of Microalgae For the Production Of Recombinant S-...mentioning
confidence: 99%